Prepregnancy Depression and Breastfeeding Duration: A Look at Maternal Age - Jordyn T. Wallenborn; Anny-Claude Joseph; Whitney C. Graves; Saba W. Masho (Journal of Pregnancy)
Background. In the United States, major depressive disorder affects one in five women aged 20-40 years. During these childbearing years, depression can negatively impact maternal behaviors that are crucial for infant growth and development. This study examined the relationship between prepregnancy depression and breastfeeding duration by maternal age. Methods. Data from Phase 7 (2012-2013) of the Pregnancy Risk Assessment Monitoring System (N=62,483) were analyzed. Prepregnancy depression was dichotomized while breastfeeding duration was categorized as never breastfed, breastfed 8 weeks or less, and breastfed more than 8 weeks. Maternal age was a significant effect modifier; therefore, results were stratified by maternal age. Multinomial logistic regression was used to obtain odds ratios and 95% confidence intervals (CI). Results. For women aged 20-24, 25-29, and 30-34 years with prepregnancy depression, the odds of never breastfeeding and breastfeeding 8 weeks or less were significantly higher than in women with no history of prepregnancy depression. Notably, among women aged 25-29 with prepregnancy depression, the odds of never breastfeeding and breastfeeding 8 weeks or less were 93% (adjusted odds ratio (AOR) = 1.93, 95% CI =1.57-2.37) and 65% (AOR = 1.65, 95% CI = 1.37-1.99) higher compared to women with no history of prepregnancy depression, respectively. Conclusions. Having a history of poor mental health before pregnancy may increase the likelihood of premature breastfeeding cessation. A woman’s mental health status before pregnancy should be considered in reproductive and prenatal care models. Efforts should be made to understand challenges women of specific age groups face when trying to breastfeed.